A laboratory study of the psychological impact of light pollution in national parks. (June 2018) - Benfield, Jacob A.; Nutt, Robert J.; Taff, B. Derrick; Miller, Zachary D.; Costigan, Heather; Newman, Peter
Abstract: Light pollution is ubiquitous in much of the developed and developing world, including rural and wilderness areas. Other sources of pollution, such as noise or motorized vehicle emissions, are known to impact the perceived quality of natural settings as well as the psychological well-being and satisfaction of visitors to those locations, but the effects of light pollution on visitors to natural settings is largely unstudied. Using experimental manipulations of light pollution levels in virtual reality simulations of three U.S. National Parks, the current study aimed to provide initial evidence of an effect on visitors. Results show that light pollution impacts a range of psychological and scene evaluation dimensions but that pristine night skies are not necessarily viewed as the ideal, likely due to being viewed as unfamiliar or unrealistic because so few have experienced the true baseline. Highlights: Laboratory experiment utilizing immersive virtual environments. 138 participants view 9 light pollution levels in forest, desert, or ocean scenes. Higher levels of light pollution decreased mood, scenic, and night-sky evaluations. No effect for location and no location by light pollution level interactions.